City of the beasts - Allende, Isabel (London : Harper Collins Publishers, 2002)
When fifteen-year-old Alexander Cold accompanies his individualistic grandmother on an expedition to find a humanoid beast in the Amazon, he experiences ancient wonders and a supernatural world as he tries to avert disaster for the Indians
Keywords: Adventure and adventures -- Fiction; Supernatural -- Fiction; Amazon river valley -- Fiction; Indians of South America -- Amazon River Valley -- Fiction